Expression of BMP and Actin Membrane Bound Inhibitor Is Increased during Terminal Differentiation of MSCs. (23rd October 2016) - Pfeifer, Christian G.; Karl, Alexandra; Berner, Arne; Zellner, Johannes; Schmitz, Paul; Loibl, Markus; Koch, Matthias; Angele, Peter; Nerlich, Michael; Mueller, Michael B.
Abstract : Chondrogenic differentiating mesenchymal stem cells (MSCs) are mimicking embryonal endochondral ossification and become hypertrophic. BMP (bone morphogenetic protein) and Activin Membrane Bound Inhibitor (BAMBI) is a pseudoreceptor that regulates the activity of transforming growth factor- β (TGF- β ) and BMP signalling during chondrogenesis. Both TGF- β and BMP signalling are regulators of chondrogenic cell differentiation. Human bone marrow derived MSCs were chondrogenically predifferentiated in aggregate culture for 14 days. Thereafter, one group was subjected to hypertrophy enhancing media conditions while controls were kept in chondrogenic medium until day 28. Histological evaluation, gene expression by PCR, and Western blot analysis were carried out at days 1, 3, 7, 14, 17, 21, and 28. A subset of cultures was treated with the BMP inhibitor Noggin to test for BMP dependent expression of BAMBI. Hypertrophic differentiated pellets showed larger cells with increased collagen 10 and alkaline phosphatase staining. There was significantly increased expression of BAMBI on gene expression and protein level in hypertrophic cultures compared to the chondrogenic control and increased BMP4 gene expression. Immunohistochemistry showed intense staining of BAMBI in hypertrophic cells. BAMBI expression was dose-dependently downregulated by Noggin. The pseudoreceptor BAMBI is upregulated upon enhancement of hypertrophy in MSC chondrogenic differentiation by a BMP dependent mechanism.